STUDI TENTANG PROFIL KETERAMPILAN BELAJAR PESERTA DIDIK DI SMA NEGERI 1 PAINAN - Sari, Nola Karmila; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The purpose of this study was to describe the study of Profiles in Learning Skills Learners develop an excellent learning skills in SMA N 1 Painan. The study was descriptive. The research was conducted in SMA N 1 Painan with a sample of 87 students. The instrument used was a questionnaire and interview guides. The research results revealed that: (1) the skills profile of learners before teaching and learning process in both categories with a percentage of 64.95%. (2) Info skills of learners in the teaching and learning process in both categories with a percentage of 70.90%. (3) The skills profile of learners after the teaching and learning process in both categories with a percentage of 68.6%. Based on the research findings, it is suggested to mentor teachers in order to improve learning skills to students about how to improve the skills of learners before starting the lesson, during the process of learning takes place and before the learning process takes place. For parents, in order to provide care and guidance to the children in improving learning skills. For principals to be able to observe how the skills learned before PBM took place, took place during and after the PBM lasts. From the above it can be concluded that the skills students learn in high school N 1 Painan that need more role of teachers and counselors to assist students in the learning process.